Strategi Pertahanan Negara dalam Mengamankan Wilayah Perbatasan di Indonesia (Studi Kasus Perbatasan Indonesia-RDTL) - Hede Uly; G. Harsono; M. Supriyatno; R. A. G. Gultom (Journal on Education, 2023)
This article describes the condition of the Indonesia-RDTL (Timor Leste) border area, starting from the history of attempts to secede from the Indonesian state, to the threats faced by Indonesia, especially the border communities in facing the worst possibilities that could occur between the two countries. Threats faced by Indonesia include military threats and non-military threats. In general, Indonesia's military strength is far superior in terms of personnel and defense equipment, while in dealing with non-military threats, the threats faced include refugees to smuggling, both narcotics smuggling and illegal firearms smuggling. The defense strategy to the policies implemented by the government are different in dealing with each threat. Policies in the form of adding security posts to improving the quality of personnel are government policy steps in dealing with military threats, while in dealing with non-military threats, policy steps taken by the government include repatriation to resettlement and improving people's living standards. In conclusion, the defense strategy and policies adopted by the government in securing the Indonesia-East Timor border area are a long-term and sustainable strategy to provide a sense of security for all Indonesian people, especially the people in the border areas.